Identification and characterization of unique tumoricidal genes in rat umbilical cord matrix stem cells - Uppalapati, Lakshmi Deepthi (Kansas State University, 2013)
Rat umbilical cord matrix stem cells (UCMSC) have been shown to exhibit a remarkable ability to control rat mammary adenocarcinoma (Mat B III) cell proliferation both in vivo and in vitro. To study the underlying mechanisms and genes involved in Mat B III growth attenuation, total RNA was extracted from the naïve rat UCMSC alone and those co-cultured with Mat B III in Transwell culture dishes. Gene expression profiles of naive rat UCMSC alone and those cocultured with Mat B III cells were investigated by microarray analysis using an Illumina RatRef- 12 Expression BeadChip. The comparison of gene expression profiles between untreated and cocultured rat UCMSC identified five up-regulated candidate genes (follistatin (FST), sulfatase1 (SULF-1), glucose phosphate isomerase (GPI), HtrA serine peptidase (HTRA1), and adipocyte differentiation-related protein (ADRP)) and two down-regulated candidate genes (transforming growth factor, beta-induced, 68kDa (TGFβI) and podoplanin (PDPN)) based upon the following screening criteria: 1) expression of the candidate genes should show at least a 1.5 fold change in rat UCMSC co-cultured with Mat B III cells; 2) candidate genes encode secretory proteins; and 3) they encode cell growth-related proteins. Following confirmation of gene expression by real time-PCR, ADRP, SULF-1 and GPI were selected for further analysis. Addition of specific neutralizing antibodies against these three gene products individually in co-cultures of 1:20 rat UCMSC:Mat B III cells significantly increased cell proliferation, implying that these gene products are produced under the co-cultured condition and functionally attenuate cell growth. Immunoprecipitation followed by Western blot analysis demonstrated that these proteins are indeed secreted into the culture medium. Individual over-expression of these three genes in rat UCMSC significantly enhanced UCMSC-dependent inhibition of cell proliferation in co-culture. These results suggest that ADRP, SULF-1 and GPI act as tumor suppressor genes, and these genes might be involved in rat UCMSC-dependent growth attenuation of rat mammary tumors.
Keywords: Umbilical cord matrix stem cells; Breast cancer; Veterinary Medicine (0778)